Water purification via removal of turbidity and bacteria using Moringa oleifera lam. Seed powder - Narayasamy, Sures (2014)
Malaysian waters are highly turbid and comprising of suspended material such as mud, heavy metals, and bacteria which is not safe for human. Most of the illnesses that are associated with waterborne diseases are cholera, diarrhea, and dysentery. Conventional chemical coagulants in water treatments plants are unsuitable because of cost (economical factor), non-biodegradable and not safe for human consumption. This study evaluated the efficiency of Moringa oleifera seeds in removing turbidity, maintaining water pH level, water color index and reducing bacterial population using most probable number method (MPN). Water samples were treated with dry season and rainy season moringa seeds and iron (ii) sulfate at 0 g/l – 4.0 g/l. The greater turbidity removal was achieved with iron (ii) sulfate (98.5 %) while drought season moringa seeds removed turbidity up to 89 % whereas rainy season moringa seeds removed turbidity by 79.7 %. Meanwhile, the water pH level slightly increases but still within drinkable range that is 6.0-8.0 for moringa treated waters but the water pH level dropped drastically to acidity level (3.0) for iron (ii) sulfate. In addition, moringa treated waters reduced bacterial population by 99 % but waters treated with iron (ii) sulfate only managed to reduce bacterial population by 74.60 %. In summary, moringa can be used as an alternative coagulant in treatment plants along with iron (ii) sulfate to purify waters.